THE ROLE OF THE MARKET IN IMPROVING THE COMMUNITY ECONOMY ACCORDING TO THE ISLAMIC ECONOMIC PERSPECTIVE (CASE STUDY OF THE SENGGOL KURIPAN MARKET IN INDONESIA) - Arinda Deviana (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2021)
A market is a place that has rules set up for the exchange of property rights and the exchange of goods between producers and consumer. Islam emphasizes that the market must stand on the principle of perfect competition. However, that does not mean that freedom is absolute. but freedom is wrapped in the frame of shari'ah. The market mechanism in Islam is the existence of market freedom in determining prices. Prices depend on the market. However, Islam does not adhere to the principle of a free market price. Islamic economics views that the market, state, and individual are in balance (iqtishad). The market is guaranteed freedom in Islam. The free market determines the methods of production and prices, there should be no disturbance that results in the destruction of the market balance.                                                                                                   Keywords : Mechanism, Market, Islam